Global publics : their power and their limits, 1870-1990 - Huber, Valeska, 1980- 1980- Herausgeber; Osterhammel, Jürgen, 1952- 1952- Herausgeber (Studies of the German Historical Institute London, 2020)
This volume combines a present-day and historical concern on the topic of global publics between the communication revolution of the 1870s and the digital age. Building on earlier theories of public spheres, Valeska Huber and Jürgen Osterhammel expand the notion of global publics not only geographically but also by charting new thematic territory, describing global publics as courts of global opinion, as market places, or as arenas for competition. As the firsthistorical volume ever to combine different facets of global publics ranging from infrastructures, the press, film and theatre to human rights politics, it brings together established and emerging authors in the field of history and from related disciplines such as geography, sociology, andliterature who explore how global publics were configured, imagined, and fragmented. In this way, Global Publics: Their Power and Their Limits not only provides a new conceptual framework and important case studies but also shows how histories of global communication might be studied in the future.